Scenarios of climate change effects in water availability within the patos Lagoon’s Basin - Schuster,Raíza Cristóvão (2020)
ABSTRACT The decision-making processes involving water resources in Brazil and in neighboring countries have been based solely on analyses of the historical behavior of hydroclimatological variables. However, this may lead to inappropriate strategies in regards to the use of natural resources, since the impact of future climate change may significantly affect the availability of water resources. This study proposes an analysis of the variation in water availability of basins within the Patos Lagoon contribution area, which may be a consequence of climatic changes predicted by CMIP5 (Coupled Model Intercomparison Project Phase 5) models, published in the most recent International Panel on Climate Change (IPCC) report. Two 30-year periods were simulated, from 2006 to 2035 and from 2051 to 2080, through the MGB-IPH hydrological model, considering two extreme greenhouse gas scenarios and twenty climate change models. A tendency of increase of the flows was verified in the simulated basin, since over 60% of the simulations indicated some percentage of average flow increase across all discretized modeling units. The analysis of the simulation results indicated that the data from climatic models HadGEM2-ES and GFDL-CM3 used as input in the hydrological model are the ones that respectively provide upper and lower flow thresholds for the ensembled simulations. A joint evaluation of the results generated by these two models, associated with the scenario of high greenhouse gas emissions, is capable of covering extreme flow scenarios making predictions considering climate change in the Patos Lagoon’s basin. Whereas the results provided by bcc-csm1, BNU-ESM and CNRM-CM5 are similar to the median of the ensemble of simulations generated by all models evaluated in this research. In addition, the northernmost region of the study area was identified as having the highest sensitivity to climate change, as projected by global models of CMIP5 published in AR5.